2005
DOI: 10.1161/01.cir.0000158434.69180.2d
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Albuminuria and the Risks of Hypertension and Blood Pressure Progression

Abstract: Background-It has been postulated that glomerular hyperfiltration and endothelial dysfunction are early features of essential hypertension that may antedate blood pressure elevation. Microalbuminuria, a marker of glomerular hyperfiltration and endothelial dysfunction, has been described in individuals with established hypertension, but its role as a biomarker of preclinical stages of this disease has not been investigated prospectively. Methods and Results-We examined the association between urinary albumin ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
154
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(172 citation statements)
references
References 55 publications
(50 reference statements)
12
154
2
4
Order By: Relevance
“…On balance, Wang et al 21 and others 20 found that low-grade albumin excretion does, in fact, predict blood pressure progression and incident hypertension in non-diabetic, normotensive individuals. 20,21 Schultz et al 43 reported similar results even in children (mean age at follow-up, 15.0 years) with type 1 diabetes mellitus, where blood pressure only rose concurrently with the onset of microalbuminuria.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On balance, Wang et al 21 and others 20 found that low-grade albumin excretion does, in fact, predict blood pressure progression and incident hypertension in non-diabetic, normotensive individuals. 20,21 Schultz et al 43 reported similar results even in children (mean age at follow-up, 15.0 years) with type 1 diabetes mellitus, where blood pressure only rose concurrently with the onset of microalbuminuria.…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14] It is regarded not only as a marker of glomerular endothelial damage, but also reflects general endothelial damage [15][16][17][18] and related arterial stiffness. 19 There is a growing body of evidence showing that low-grade albuminuria, well below 3.5 mg mmol À1 , is associated with blood pressure increase, 20,21 endothelial dysfunction, 22,23 arterial stiffness 24 and the development of cardiovascular disease 25 in healthy non-diabetic individuals without chronic kidney disease. Unfortunately, the above evidence is predominantly from Caucasian population groups.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, recent studies conducted in type 2 diabetic patients revealed that even very low UAE rates, below those conventionally accepted as the lower limit to define microalbuminuria (o30 mg per 24 h), were also associated with increased mortality. 15 Similarly, in non-diabetic subjects, albuminuria of o30 mg day À1 was found associated with older age, male gender, smoking, obesity, elevated blood pressure, left ventricular hypertrophy, dyslipidaemia, hyperinsulinaemia, salt sensitivity, lack of nocturnal BP dipping [15][16][17][18][19] and increased risk of coronary heart disease and death 10,15,[20][21][22][23][24][25] (Table 1). In non-diabetic hypertensive individuals with left ventricular hypertrophy, the risk for cardiovascular morbidity and mortality increased continuously as the UAE increased.…”
mentioning
confidence: 96%
“…14 In hypertensive subjects, albumin-to-creatinine ratios of 10-16 mg mg À1 , 2.5-to 3-fold lower than the cutoff for defining microalbuminuria, predicted increased risk of cardiovascular mortality. 7 Such a low level of albuminuria was also found to predict progression to hypertension in non-diabetic, non-hypertensive subjects, 22 and was associated with a 2.3 times greater adjusted risk of developing ischaemic heart disease. 21 In middle-aged non-hypertensive, nondiabetic Framingham Offspring Study participants, 26 those with an albumin-to-creatinine ratio of X3.9 mg mg À1 for men and X7.5 mg mg À1 for women, well below the threshold for microalbuminuria, experienced a nearly three-fold risk of cardiovascular disease ( Table 1).…”
mentioning
confidence: 98%
See 1 more Smart Citation